Blue Economy Implementation As A Strategy For Sustainable Coastal Economic Development - Syamsul Arifin; Irviandi Yudhotomo; Toong Hai Sam; Miftahul Jannah S (International Journal of Economics, Science, and Education, 2026)
Purpose: This study aims to review the role of the Blue Economy in supporting sustainable coastal and marine development by integrating economic growth, environmental sustainability, and social welfare. Design/Methodology/Approach: A systematic literature review (SLR) was conducted using peer-reviewed articles and international reports published between 2015 and 2025. Relevant literature was collected from Scopus, Web of Science, and Google Scholar and analyzed using thematic synthesis. Findings: The results indicate that the Blue Economy is driven by sustainable fisheries, marine tourism, renewable ocean energy, marine conservation, and efficient resource utilization. Government support, technological innovation, stakeholder collaboration, and sustainable financing are identified as key factors influencing successful implementation. Furthermore, Blue Economy practices contribute to economic growth, employment creation, environmental protection, and the welfare of coastal communities. Research Limitations/Implications: This review is limited to selected databases and English-language publications. Future research should focus on empirical studies examining Blue Economy implementation in developing countries. Practical Implications: The findings provide insights for policymakers and practitioners in developing sustainable marine resource management strategies. Originality/Value: This study offers a comprehensive overview of Blue Economy research and identifies opportunities for future sustainable development initiatives. Paper Type: Literature Review Keywords: Blue Economy; Sustainable Development; Marine Resources; Coastal Development; Environmental Sustainability